Trading robots on the Stock market (Путеводитель предпринимателя, 2020)
This article is devoted to the automation trading on the stock markets, it’s certification, and statistics of trading robots on the stock market. Because this occurrence is most recent, the main results were presented on the own opinion based on observations in the working process, from various forums and seminars under the question.